YARGITAY İÇTİHATLARI IŞIĞINDA ÇOCUĞUN CİNSEL İSTİSMARI SUÇU AÇISINDAN TEŞEBBÜS VE İŞTİRAK HÜKÜMLERİNİN UYGULANMASI - (:unkn) unknown (My University, 2019)
Genel suç teorisi içerisinde niteliği itibariyle cezalandırılabilirliğigenişleten hükümler içeren suça teşebbüs ve sorumluluğu genişleteniştirak kurallarının uygulanması, çocuğun cinsel istismarı suçu yönündendiğer suçlara nazaran zorluklar içermektedir. Türk ceza hukukunda cinsel istismar suçunu düzenleyen TCK’ın 103’ncü maddesinde yapılan sondeğişiklikler ve bu bağlamda suç tipindeki değişikliğe göre çeşitlenenYargıtay uygulamaları da meseleye ayrı bir boyut kazandırmaktadır. Öteyandan 765 sayılı TCK döneminden beri süre gelen tartışmaların birkısmının da halen devam ettiği anlaşılmaktadır. Meseleyi uluslararasıdüzeyde ele alan Avrupa Konseyi Çocukların Cinsel Sömürü ve İstismarına Karşı Korunması Sözleşmesi’nin (Lanazorate Sözleşmesi) ise busuç için teşebbüs ve iştirak (yardım ve azmettirme) halleri açısından,ulusal mevzuat ve uygulamamızı genişletecek hükümler içerdiği görülmektedir.

The implementation of participation and criminal attempt rules that includes provisions extending punishablity and liabilty owing to their characteristic in general theory of crime is relatively difficult with regard to this crime. The last amendments ofthe article 103 ofthe Turkish Criminal Code which regulates the crime ofchild sexual abuse and the jurisprudence ofthe Court ofCassation diversified according to the changed tpicality ofthe crime add a new dimension.. On the other hand, some of the long-standing disputes on this matter are still being under discussion. It is seen that Council of Europe Convention on the Protection of Children against Sexual Exploitation and Sexual Abuse includes provisions which expand national legislation and its implementation in terms ofparticipation and criminal attempt rules.
THE IMPLEMENTATION OF THE PROVISIONS OF CRIMINAL ATTEMPT AND PARTICIPATION WITH REGARD TO THE CRIME OF CHILD SEXUAL ABUSE IN THE LIGHT OF JURISPRUDENCE OF THE COURT OF CASSATION